Facilities Quality Assistance at the National Street Soccer Championship at Jasdam II Sriwijaya - Safitra, Novin Aidil; Taroreh, Bangkit Seandi; Fikri, Aprizal (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of this community service activity is to increase knowledge of the quality of facilities at the National Street Soccer Championship at Jasdam II Sriwijaya. The method is through mentoring with stages, namely 1) planning, 2) implementation, 3) evaluation. The subject is the team implementing the National Street Soccer Championship at Jasdam II Sriwijaya, totaling 30 people. The data collection technique uses a questionnaire with quantitative percentage data analysis. The result of community service activities was an increase in the knowledge of the team implementing the National Street Soccer Championship at Jasdam II Sriwijaya by 100% (30 people). Community service activities at Jasdam II Sriwijaya provide enormous benefits to the community. On the first day, the material on the quality of facilities in the preliminary round of the National Street Soccer Championship discussed the quality of the facilities, supervision of the facilities for the preliminary round of all teams that will compete according to the schedule of the championship committee to win the competition to enter the next round. On the second day, quality of facilities, monitoring of facilities for the semi-final and final rounds of the National Street Soccer Championship discussed the semi-final round consisting of 4 teams that will compete to win so they can play to the next stage, namely the final, the final is the last stage of the championship for determine the winner of the 2 teams that will compete.